2011
DOI: 10.1093/carcin/bgr293
|View full text |Cite
|
Sign up to set email alerts
|

Decorin-mediated inhibition of colorectal cancer growth and migration is associated with E-cadherin in vitro and in mice

Abstract: Previous studies have shown that decorin expression is significantly reduced in colorectal cancer tissues and cancer cells, and genetic deletion of the decorin gene is sufficient to cause intestinal tumor formation in mice, resulting from a downregulation of p21, p27(kip1) and E-cadherin and an upregulation of β-catenin signaling [Bi,X. et al. (2008) Genetic deficiency of decorin causes intestinal tumor formation through disruption of intestinal cell maturation. Carcinogenesis, 29, 1435-1440]. However, the reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
108
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(118 citation statements)
references
References 38 publications
(42 reference statements)
10
108
0
Order By: Relevance
“…5), which was consistent with previous studies reporting that HDAC6 is required for β-catenin activation in colon cancer cells (20,21). Whether TSA-mediated EMT induction and inhibition, elevation of β-catenin mRNA levels and inhibition of β-catenin protein levels are associated with other signaling pathways, such as the decorin-β-catenin-E-cadherin signaling pathway (22), remains unclear and is currently under investigation.…”
Section: Tsa Increases the Expression Levels Of Mesenchymal Markers Asupporting
confidence: 89%
“…5), which was consistent with previous studies reporting that HDAC6 is required for β-catenin activation in colon cancer cells (20,21). Whether TSA-mediated EMT induction and inhibition, elevation of β-catenin mRNA levels and inhibition of β-catenin protein levels are associated with other signaling pathways, such as the decorin-β-catenin-E-cadherin signaling pathway (22), remains unclear and is currently under investigation.…”
Section: Tsa Increases the Expression Levels Of Mesenchymal Markers Asupporting
confidence: 89%
“…Compelling evidence has shown that DCN contributes to inhibition of tumor growth and metastasis (13,(15)(16)(17)(18)(19)34). Goldoni et al reported that DCN can display an anti-metastatic role in breast cancer (16).…”
Section: Discussionmentioning
confidence: 99%
“…Goldoni et al reported that DCN can display an anti-metastatic role in breast cancer (16). Bi et al demonstrated that DCN may act as a tumor suppressor gene (15) and mediate inhibition of colorectal cancer growth and migration (13). Among soft tissue tumor patients with recurrent or metastatic lesions, lower levels of DCN were expressed in secondary lesions than those in primary lesions (17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations